PERHITUNGAN PREMI ASURANSI JOINT LIFE DENGAN MODEL VASICEK DAN CIR - WIGUNA, I MADE WAHYU; JAYANEGARA, KETUT; WIDANA, I NYOMAN (E-Jurnal Matematika, 2019)
Premium is a sum of money that must be paid by insurance participants to insurance company, based on  insurance contract . Premium payment are affected by interest rates . The interest rates change according to stochastic process. The purpose of this work is to calculate the price of joint life insurance premiums with Vasicek and CIR models. The price of a joint life insurance premium with Vasicek and CIR models , at the age of the insured 35 and 30 years has increased until the last year of the contract. The price of a joint life insurance premium with Vasicek model is more expensive than the premium price using CIR model.